The Effect of Perceptions of Ease, Benefits, Risk, Trust and Convenience on Customer Interest in Using Internet Banking - Antoni, Antoni; Fitriano, Yun; Prawitasari , Andriyani (Journal of Management, Economic, and Accounting, 2025)
The aim of this research is to determine the influence of perceived ease, benefits, risks, trust and comfort on customers' interest in using internet banking. This type of research uses quantitative. The data collection method in this research used a questionnaire technique, with a sample of 100 respondents.The research results show that multiple linear regression Y = 2.694 + 0.155 X1 + 0.335 X2 + 0.074 X3 + 0.382 Where the coefficient is positive, meaning that there is a positive or unidirectional relationship between the variables perception of convenience (X1), benefits (X2) risk (X3), trust (X4), comfort (X5) the value is 0 (zero), customer interest (Y) in using the internet Banking. The research results show that the perception of convenience test (XI) shows tcount 3.285 > ttable 1.659 and significance 0.001 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that perception of convenience has a positive and significant effect on customers' interest in using internet banking. The results of the benefits test (X2) show tcount 2,650 > ttable 1,659 and significance 0.009 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning benefits have a positive and significant effect on customers' interest in using internet banking. The results of the risk test (X3) show tcount 2.575 > ttable 1.659 and significance 0.019 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning risk has a positive and significant effect on customers' interest in using internet banking. The results of the trust test (X4) show tcount 3,119 > ttable 1,659 and significance 0.002 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that trust has a positive and significant effect on customers' interest in using internet banking. The results of the comfort test (X5) show tcount 1,260 > ttable 1,659 and significance 0.211 > 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that comfort has no positive and significant effect on customers' interest in using internet banking. Based on the comparison of the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 11,859 > 2.19, so it is concluded that accepting the hypothesis, meaning that there is a simultaneous influence between perceived convenience (X1), benefits (X2), risks (X3), trust (X4) , convenience (X5) on customer interest (Y) in using internet banking. This can be seen at the significance level of 0.000 <0.05